DISCOURSE ANALYSIS OF CHARACTER DEVELOPMENT IN J.K. ROWLING'S HARRY POTTER SERIES: LINGUISTIC AND NARRATIVE TECHNIQUES - Putri Adelia; Inayah Safani; Juwita Permatasari; Desman Silitonga (Adisam Publisher, 2024)
J.K. Rowling's Harry Potter series has captivated millions of readers worldwide, particularly through the multifaceted character of Harry Potter himself. This research employs critical discourse analysis to examine how Rowling utilizes language and narrative techniques to depict and develop Harry's character across the seven-book series. Drawing on theoretical frameworks from narrative theory and discourse analysis, the study explores Harry's evolution from a vulnerable orphan to a courageous leader, analyzing both micro-level linguistic features and macro-level narrative structures. By examining themes of identity, morality, and heroism as portrayed through Harry's interactions and internal monologues, this research illuminates the nuanced strategies through which Rowling shapes Harry Potter's persona and resonates with young adult audiences. This analysis contributes to literary studies by elucidating the intricate relationship between language, character development, and reader engagement in young adult literature.